Association between genotypes of \(TLR4\) gene rs2149356 polymorphism and serum level of il-6 in Vietnamese patients with gout - Xuan, Nguyen Thi; Ha, Le Thuy; Chung, Dang Thanh (Academia Journal of Biology, 2021)
Gout is an inflammatory type of arthritis caused by the deposition of crystals of monosodium urate monohydrate (MSU) in the joints. The arthritis is mediated by the release of pro-inflammatory cytokines including IL-1β, TNF-α and IL-6 by leukocytes including macrophages. Toll-like receptor (TLR)4 is expressed in the immune cells to initiate immune response by inducing activation of signaling molecules involved in the transcription of nuclear genes. In this study, mutational analysis of TLR4 gene was examined to determine the prevalence of gene polymorphism in Vietnamese patients with gout. Molecular analysis of this gene was investigated by PCR amplification and direct DNA sequencing. Level of serum cytokines was measured by ELISA. As a result, no significant difference in frequency of TLR4 gene rs2149356 polymorphism was observed between the patient and control groups. Importantly, level of IL-6 was significantly higher in patients carrying CG genotype as compared with patients carrying TG and TT genotypes of TLR4 gene rs2149356 polymorphism and the patients carrying GG genotype exhibited higher IL-6 level than healthy individuals. The GG genotype of TLR4 gene rs2149356 polymorphism in gout patients were sensitive to IL6-induced inflammatory response. The effect is expected to affect the immune response to treatment for gout patients.